Challenging concepts in oncology - Bhattacharyya, Madhumita; Payne, Sarah; McNeish, Iain ([Oxford] : Oxford University Press, 2015)
Providing the inside track on how the experts approach and deal with real-world clinical scenarios,'Challenging Concepts in Oncology' contains wide-ranging and in-depth reviews of contemporary and often contentious topics in the world of oncology today. With a case-based approach and expert commentary throughout, complex patient presentations are discussed from a multidisciplinary perspective and all the angles necessary for accurate assessment, diagnosis, and management are fully considered and explored.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 15, 2015).
Keywords: Oncology